PERAN KELUARGA DALAM MENINGKATKAN MOTIVASI BELAJAR ANAK - Pakinah Herliani (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2015)
Parents as educators must also keep children's personal development as a determinant in education in accordance with the treatment period or age levels and thinking ability of children.We as students are not separated from the motivation to learn, so I as speaker expects the reader siding with this paper that we may mengetahuai about how the role of parents in improving learning motivation in students / children. Although this paper is far from perfect but when we read and understand it, hopefully many benefits that we can take.